Внутрішня мотивація до навчання студентів спеціальності "Фізична культура і спорт" - Борейко, Наталя Юріївна; Азаренкова, Любов Леонідівна (Національний педагогічний університет ім. М. П. Драгоманова, 2017)
У статті розглянуто питання внутрішньої мотивації студентів до навчання, проаналізовано поняття мотивації та внутрішньої мотивації, визначено рівень мотивації до навчання у студентів та розглянуто більш детальне відношення до дисциплін студентів спеціальності "Фізична культура і спорт".

In Bologna system of education, training consists of loans, which include contact hours and independent work of students. Therefore, intrinsic motivation is relevant, the student must comply with professional competence, be creative professional tasks, taking pleasure in learning. Students who are intrinsically motivated to study in the field of physical culture and sports, mastering professional skills, knowledge and abilities will be able to more competitiveness in the labor market. So study the problem of internal motivation to learn is relevant. To assess the level of intrinsic motivation in students of specialty "Physical Culture and Sports" was tested by the method of diagnosis for orientation learning motivation by Dubovytskiy T.D. 34 students 4 courses of specialty "Physical culture and sport" NTU "KPI" took part in research. Academic subjects for testing were taken from the curriculum of Bachelor specialty "Physical culture and sport" seventh term: "Theory and methods of teaching basic types of sports activities", "Organization of Physical Culture", "Fundamentals of medical knowledge", "Basic Research", "Information support of physical culture." The internal motivation for learning makes it possible to enjoy the received information and the understanding of its purpose in physical culture and sports. Studying intrinsic motivation for learning in students of specialty "Physical culture and sport", it was found that 60% of students consider obtaining knowledge valuable and interesting because most students intrinsic motivation high level. But 20% of students were found difficulties in study subjects (most of these students because of competitive training regime and miss a lot of classes. They acquire theme on their own, that making it difficult to study the material in the future).
Internal motivation for training of students of specialty "Physical culture and sports"
Keywords: навчальний процес; пізнавальна активність; тестування; internal motivation; students; testing; training